Linking employee green behavior and green innovation to green human resource management: Insights from a construction company - Navila Amira Dewi; Furqon Syarief Hidayatulloh; Pudji Muljono (Universitas Nusa Cendana, 2026)
This study aims to examine the influence of employee green behavior and green innovation on green human resource management within a construction company context. A quantitative explanatory approach was employed, using survey data collected from employees and analyzed through partial least squares structural equation modeling. The findings indicate that both employee green behavior and green innovation play important roles in shaping green human resource management practices, with employee driven environmental behavior emerging as the more influential factor. Together, these variables explain nearly half of the variation in green human resource management, highlighting the importance of behavioral and innovation based mechanisms in institutionalizing sustainability practices. The study contributes to the literature by adopting a bottom up perspective, demonstrating that green human resource management may develop in response to employee actions and innovation initiatives rather than solely through managerial directives. This research is limited to a single organizational context, which may restrict generalizability. Future studies are encouraged to incorporate additional organizational factors and broader industry settings to enrich understanding of green human resource management development. Keywords: Green Human Resource Management; Employee Green Behavior; Green Innovation